Evaluation studies of a sensing technique for electrostatic charge polarity of pharmaceutical particulates. Issue 5 (1st August 2016) - Hussain, Tariq; Deng, Tong; Bradley, Michael Samuel Arthur; Armour‐Chélu, David; Gorman, Terry; Kaialy, Waseem
Abstract : Electrostatic charge due to inter‐particle and particle‐to‐wall contacts may generate significant hazards during the processing of particulates within the pharmaceutical industry. Although charge behaviour of particulates is erratic and not easy to predict, it would be desirable to characterise the tendency of tribocharging prior to manufacturing. The work reported in this study concentrates on a new and novel technique for the detection of the active ingredient and excipient in a bipolar material. Three different case studies are presented for demonstration of the applicability of the method in different practical situations. Work confirmed through an experimental rig set‐up indicates that materials that accumulate opposite charge via contact and rubbing can be detected from their charge sign as well as their relative magnitude. The results reported clearly demonstrated that the developed method for charge characterisation is a useful tool to understand how the charges are distributed in a population of particles showing a number of advantages over conventional methods.